Synthetic chemistry and synthetic biology approaches to low oxidation state taxanes - Marsh, Benjamin J. (2017)
This thesis details work towards the efficient production of low oxidation state taxanes either by synthetic biology or synthetic chemistry. With over 400 natural taxanes isolated to date, many low oxidation state taxanes have been eclipsed by the intense interest in Taxol®. Some of these low oxidation state taxanes have important medicinal properties, many are currently unexplored. Chapter I introduces the taxane family of natural products, their biosynthesis and biological activity. Chapter II documents our efforts to utilise synthetic biology to rapidly access low oxidation state taxanes. In this chapter we describe the semi-synthesis of a novel oxa-cyclotaxane (OCT2) and 5α-hydroxytaxadiene, both low oxidation state taxanes. Here we also report that taxadiene, extracted from genetically modified tomato fruit, can undergo epoxidation and rearrangement with a reduced iron porphyrin to form the same products encountered when taxadiene 5α-hydroxylase is expressed in foreign organisms. We conclude that the established free radical mechanism, based heavily on speculation, is most probably incorrect in favour of an epoxidation/ rearrangement mechanism. Chapter III describes our chemical synthesis of low oxidation state taxanes utilising carbon building blocks from renewable sources. We make use of the well-established Diels-Alder approach to construct the A and B taxane rings simultaneously, culminating in the synthesis of the natural product 5α-hydroxytaxadiene. This chapter then goes on to present both our work towards an asymmetric synthesis of taxanes utilising Yamamoto’s chiral BrØnsted acid catalyst and our efforts in the manipulation of taxane oxidation both by reduction and C-H oxidation.